Penerapan Metode Profile Matching untuk Menunjang Keputusan Seleksi Penerimaan Anggota pada Perusahaan Marikator - Widia Ramadhani; Yuliwanda Anggi Kusumastuti; Elvi Fetrina; Qurrotul Aini; Meinarini Catur Utami (Journal of Applied Computer Science and Technology, 2025)
The process of placing members in the XYZ organization is not optimal due to errors in placement or mismatches between fields and the positions assigned to its members. This is evidenced by members lacking maximum competence in their designated divisions, leading to slow organizational performance. Therefore, optimal human resource management in an organization requires selecting members with the right profiles to enhance operational performance. This study aims to determine a ranking and identify the best candidates for new member selection by applying the profile-matching method in the recruitment process of the XYZ organization. This approach considers criteria such as CVs, short essays, and interviews, using prospective member data comprising 19 (nineteen) individuals as the population and 5 (five) as the sample. Profile matching is a systematic approach for comparing the suitability of prospective member profiles against predefined criteria, enabling a more detailed and objective evaluation. This method helps identify competence gaps between candidates and expected criteria and minimizes the risk of placement errors within the organization. The calculation process is carried out using Microsoft Excel and a simple program developed with Python, utilizing Google Colab as the code editor. The study results indicate that the profile-matching method effectively identifies prospective members who best align with the organization's qualifications. Among the five candidates evaluated, Candidate 1 achieved the highest final score of 4.0556, indicating the most optimal suitability with the established criteria.